Rancang Bangun Aplikasi E-Disucission Darmajaya Berbasis Mobile - Mutiara, Suci; Saleh, Sushanty; Arnande, Muhammad Fivo (TEKNIKA, 2025)
arguments to strengthen their views. In lectures, lecturers use the discussion method as a medium for interaction between students and also to train their mindset, by presenting new cases that they have never encountered. Therefore, an online discussion platform is needed, namely the E-Discussion Application. This application is designed to make it easier for students to discuss online more efficiently and effectively, as well as being a means of discussion and sharing information in the IIB Darmajaya campus environment. The development of the E-Discussion Application was carried out using the waterfall method with the Golang, ReactJS, and Flutter programming languages. The application design uses the UML (Unified Modeling Language) model, which consists of use case diagrams, activity diagrams, and class diagrams. Testing of the application was carried out using the Black-Box Testing method, which showed that the features in the application functioned well and could be run on various devices optimally. The results of the study showed that the E-Discussion Application was able to facilitate students in conducting online discussions more easily.